Augmented Eccentric Connectivity Index of Some Thorn Graphs - De, Nilanjan (International Journal of Applied Mathematical Research, 2012)
The augmented eccentric connectivity index is defined as the summation of the quotients of the product of adjacent vertex degrees and eccentricity of the concerned vertex of a graph which is a generalization of eccentric connectivity index. In this paper we present explicit expressions for the values of augmented eccentric connectivity indices of some particular thorn graphs like thorn path, thorn cycle and thorn star and then consider a particular thorn star, dendrimers.